Environmental and Economic Clustering of Indonesian Provinces: Insights from K-Means Analysis - Noviandy, Teuku Rizky; Hardi, Irsan; Zahriah, Zahriah; Sofyan, Rahmi; Sasmita, Novi Reandy; Hilal, Iin Shabrina; Idroes, Ghalieb Mutig (Heca Sentra Analitika, 2024)
Indonesia's archipelago presents a distinctive opportunity for targeted sustainable development due to its complex interplay of economic advancement and environmental challenges. To better understand this dynamic and identify potential areas for focused intervention, this study applied K-means clustering to 2022 data on the Air Quality Index (AQI), electricity consumption, and Gross Regional Domestic Product (GRDP). The analysis aimed to delineate the provinces into three distinct clusters, providing a clearer picture of the varying levels of economic development and environmental impact across the nation's diverse islands. Each cluster reflects specific environmental and economic dynamics, suggesting tailored policy interventions. The results show that for provinces in Cluster 1, which exhibit moderate environmental quality and lower economic activity, the introduction of sustainable agricultural enhancements, eco-tourism, and renewable energy initiatives is recommended. Cluster 2, marked by higher economic outputs and moderate environmental conditions, would benefit from the implementation of smart urban planning, stricter environmental controls, and the adoption of clean technologies. Finally, Cluster 3, which includes highly urbanized areas with robust economic growth, requires expanded green infrastructure, improved sustainable urban practices, and enhanced public transportation systems. These recommendations aim to foster balanced economic growth while preserving environmental integrity across Indonesia’s diverse landscapes.